2017
DOI: 10.1111/1750-3841.13631
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Contamination of Rice in China

Abstract: Mycotoxin contamination in rice is generally lower than in other cereals such as corn or wheat. However, over 65% of the population in China consumes rice as a staple food. Due to the diversity of the climate across China, the southern region is characterized by high temperatures and humidities, especially in rainy season. Such conditions are optimal for the growth of fungi. The accumulative and transferrable characteristics of fungi mycotoxins pose a great potential threat as confirmed by high incidences of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…ZEA was also quantified at 53.4% of the rice samples at an average level 10.6 µg/kg, DON in 28% of the samples at an average level of 18.9 µg/kg, and FB 1 and FB 2 were found in 14.3% and 4.8% at concentrations of 0.2 and 6 µg/kg, respectively. Sun et al [ 36 ] reported contents of AFB 1 in rice and the contents were less than 5 µg/kg, while 7% of samples were detected as exceeding the national maximum residue limit of 10 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…ZEA was also quantified at 53.4% of the rice samples at an average level 10.6 µg/kg, DON in 28% of the samples at an average level of 18.9 µg/kg, and FB 1 and FB 2 were found in 14.3% and 4.8% at concentrations of 0.2 and 6 µg/kg, respectively. Sun et al [ 36 ] reported contents of AFB 1 in rice and the contents were less than 5 µg/kg, while 7% of samples were detected as exceeding the national maximum residue limit of 10 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins comprise a structurally diverse family of naturally occurring, fungal-elaborated toxins, many of which have been strongly implicated as chemical precursors for toxicity in humans and animals (Pereira et al 2014;Sun et al 2017). The significance of mycotoxin-induced health effects derives from the natural occurrence of mycotoxins as contaminants of crops and food, and the possibility of exposure across all ages.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%
“…It has been hypothesized that serum microRNAs might correlate with toxicity of carcinogen such as AFB1. Therefore, in the present study, we conducted a case-control study to screen and analyze potential serum microRNAs for genic toxicity testing of AFB1 in a high-AFB1 exposure area, Guangxi area of China [4,48]. Our results proved that serum microRNAs such as miR-4651 and miR-382-5p were significant and linearly associated with the amounts of AFB1-DNA adducts in the cancerous tissues; moreover, increasing serum levels of these two microRNAs modified the risk of TP53M.…”
Section: The Serum Micrornas and Afb1-induced Genic Toxicitymentioning
confidence: 99%
“…Because A. parasiticus and A. flavus usually multiply under hot and humid conditions, AFB1 is as a contaminant of human food (including core, peanuts, soya sauce, and fermented soy beans) in tropical areas [1][2][3][4]. Increasing evidence has shown that AFB1 has three toxicological effects: (a) the attraction of specific organs, especially liver; (b) genotoxicity, mainly inducing the formation of the hot-spot mutation of p53 gene (especially mutation at the codon 249) and AFB1-DNA adducts; and (c) carcinogenicity, primarily causing hepatocellular carcinoma (HCC) [4][5][6][7][8][9][10][11]. Studies have shown that DNA damage induced by AFB1 plays the central role of carcinogenesis of HCC related to AFB1 in the toxic studies [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%